Perkembangan dan Kesahihan Hadis Dari Awal Islam Hingga Zaman Post Truth - Muhammad Alfatih Suryadilaga, Teuku Amnar Saputra (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2020)
The Post Truth era has made truth relative from a personal point of view not based on scientific facts. Freedom of information access makes the quality not proportional to the existing quantity. This relative truth has implications for the development of hadith which has been consumed by Muslim World in general. From the historical point of view, the modification of the hadith is inseparable from the interests of three Islamic thought orientations, namely Syiah, Ahlusunnah Wal Jamaah and Khawarij. The purpose of this study is to map the history of the development of the hadith from the time of the Prophet Muhammad and how the truth of the traditions used by the community from the time of the Prophet Muhammad to the Post Truth era. The results of this study indicate that the distribution of hadith originated in the early days of Islam, but not in official writing. Then came the official codification period in the caliph Umar bin Abdul Aziz II century Hijri. In the next period the hadith is recorded in the form of books and in the global era the hadith has been in the form of a website to the implications that can be used through smartphones. But in terms of the truth of the hadith in the Post Truth Era is still influenced by the interests of related parties so that the truth must be reviewed. Seeing the many uses of hadith in accordance with the wishes of the stakeholders. The interests are in the form of political interests and the interests of content providers with commercial purposes in various forms such as applications, dissemination on social media.